Pullulan production by Aureobasidium pullulans cells immobilized in chitosan beads. Fungal pullulan production by immobilized cells - West, Thomas P (Folia microbiologica, 2011)
Fungal cells of Aureobasidium pullulans ATCC 201253 were immobilized by entrapment in chitosan beads, and the immobilized cells were investigated for their ability to produce the polysaccharide pullulan using batch fermentation. The 1% chitosan-entrapped fungal cells were capable of producing pullulan for two cycles of 168 h using corn syrup as a carbon source. Pullulan production by the immobilized cells increased by 1.6-fold during the second production cycle (5.0 g/l) relative to the first production cycle (3.1 g/l) with the difference in production being statistically significant after 168 h. The productivity of the immobilized cells increased during the second production cycle while its pullulan content decreased. The level of cell leakage from the support remained unchanged for both production cycles.
Keywords: Glucans; Ascomycota; Carbon; glukany; Chitosan; Fermentation; fermentace; uhlík; Cells, Immobilized; chitosan; imobilizované buňky